The Rate of Catheter-Related Infections using Metal Coated Central Venous Catheters; a Letter to Editor - Ardehali, Seyed Hossein; Jahangirian, Mona; Fatemi, Alireza (Archives of Academic Emergency Medicine, 2019)
Blood infections due to intravenous catheters make up about 10% – 15% of hospital infections (1). In 2009, Centers for Disease Control and Prevention (CDC) reported the rate of blood infections related with using central venous catheter in the intensive care unit (ICU) to be 1.65 in 1000 catheters per day (2). Mortality due to infections related to central venous catheters has been reported to be between 12% and 25% in different studies. These infections have increased the duration of hospitalization by 12 days (3, 4). Different approaches have been proposed for reducing these infections, among these approaches using aseptic methods, preventive antibiotics, disposable tools, and training the staff can be pointed out (5-7). Among the methods considered in this regard is using catheters coated with antiseptic agents, antibiotics, and metals such as silver and platinum (8). Some studies have suggested using these methods for reducing the mentioned infections and their consequences; however, their use is not currently agreed upon and their effect on reducing the infections caused by intravenous tools is still being studied.